Dual carbon-confined Na2MnPO4F nanoparticles as a superior cathode for rechargeable sodium-ion battery. Issue 16 (November 2019) - Ling, Rui; Cai, Shu; Shen, Kaier; Sang, Zhiyuan; Xie, Dongli; Sun, Jiayue; Xiong, Kunzhou; Guo, Jinze; Sun, Xiaohong
Abstract: Na2 MnPO4 F has drawn worldwide attention as cathode materials for sodium-ion batteries with great promise due to its high theoretical capacity (124 mAh g −1 ) and working voltage plateau (3.6 V). Unfortunately, its electrochemical performances are largely limited by the intrinsic low electron conductivity and sluggish diffusion of Na + . Herein, a reduced graphite oxide nanosheets and nano-carbon co-modified Na2 MnPO4 F nanocomposite is prepared via a simple hydrothermal method. And the composite possesses a three-dimensional "pellets-on-sheets" structure, in which core-shell structured nanoparticles (Na2 MnPO4 F nanoparticles coated by carbon coating layers) are uniformly anchored on the surface of well-dispersed reduced graphite oxide nanosheets. Such unique structure is favorable for fast Na + and electron transports and supplies sufficient active sites for Na + insertion. As the cathode of sodium-ion battery, the as-prepared dual carbon-modified Na2 MnPO4 F composite exhibits a super discharge capacity of 122 mAh g −1 at 0.05 C and high rate-performance (42 mAh g −1 at 2 C) as well as long cycle performance (77% capacity retention after 200 cycles at 0.1 C). Meanwhile, it presents two obvious potential platforms of about 3.7 V and 3.5 V during the charge and discharge process, respectively, revealing its potential applications in high energy density batteries.